Analysis of The Influence of Market Consumption Behavior and Economic Conditions on SME Business Performance - Kushariyadi, Kushariyadi; Yani, Indri; Silamat, Eddy; Nistia Sari, Titis; Reza Aulia, Muhammad (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
This research aims to provide a comprehensive analysis of the influence of business strategy on consumer behavior, especially upper and middle class consumers. This research uses a qualitative approach with a case study design. Research data was collected through interviews, field observations and documentation. The research results show that the management team of SMEs must improve and adjust their business strategy, this is absolute and must be done immediately because the current business strategy is considered to no longer meet market expectations. This strategy must be adjusted, reviewed and refined over time to attract upper middle class consumers who seek an exclusive shopping experience while maintaining a level of product and price diversity. The research results also suggest that SME managers understand the differences in shopping behavior between the lower class who focus on efficiency and price, and the upper middle class who are not sensitive to price changes and focus more on a more personalized shopping experience. Changes in social structure and macroeconomic factors, such as increasing incomes and decreasing unemployment, also influence purchasing power and demand. Management must adapt by adjusting its offerings and infrastructure to meet the needs of different market segments and be able to respond quickly to changes in social structure and demand which can be very varied and fluctuating.